Biogenic Nanoparticle Synthesis Using Ganoderma Macrofungi and Its Biomedical and Environmental Applications (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Ganoderma is a notable Indian conventional mushroom utilized in different ethnomedicinal practices. New advancements connected with this mushroom and their exercises are consistently reported. A few researchers working with spores of this therapeutic mushroom however data of this species are still limited. This review describes about the main advances for the extraction of biocomponents and their pharmacological and cell protective effects on health system because of their importance in drug discovery. Recognizing the bioavailability of the naturally dynamic parts of G. lucidum after oral administration, and very little has been published in this area. Although single compounds can mediate a biological effect, nutraceuticals often act through the synergistic activity of multiple metabolites. It is significant to gain a better understanding of the bioavailability of the active components in this mushroom under various conditions to ensure robust study designs and to maximise consumer advantage. Nanoparticles derived from macro fungi, including various mushroom species like Ganoderma spp. are well known to possess immune-modulatory, high nutritional, antimicrobial, antioxidant, and anticancerous effect. Fungi have intracellular metal uptake capacity and supreme wall binding ability. In this review also discussed the nanoparticles synthesis from micro fungi of Ganoderma species and mechanism of nanoparticles derived from the micro fungus.